2016
DOI: 10.1128/jvi.00384-16
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Human Cytomegalovirus Proteins pUL77 and pUL93 Are Structural Components Necessary for Viral Genome Encapsidation

Abstract: Several essential viral proteins are proposed to participate in genome encapsidation of human cytomegalovirus (HCMV), among them pUL77 and pUL93, which remain largely uncharacterized. To gain insight into their properties, we generated an HCMV mutant expressing a pUL77-monomeric enhanced green fluorescent protein (mGFP) fusion protein and a pUL93-specific antibody. Immunoblotting demonstrated that both proteins are incorporated into capsids and virions. Conversely to data suggesting internal translation initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 80 publications
(119 reference statements)
9
55
1
Order By: Relevance
“…We recently discovered that pUL93 is required for viral genome cleavage and packaging, similar to its homolog pUL17 in HSV-1 (17). These findings are supported by another recent study which found that both pUL93 and pUL77 are required for genome encapsidation (18). pUL77 has been found to bind double-stranded DNA and interact with DNA-packaging motor components as well as with major capsid protein, suggesting that pUL77 helps retain viral DNA during capsid assembly (19).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…We recently discovered that pUL93 is required for viral genome cleavage and packaging, similar to its homolog pUL17 in HSV-1 (17). These findings are supported by another recent study which found that both pUL93 and pUL77 are required for genome encapsidation (18). pUL77 has been found to bind double-stranded DNA and interact with DNA-packaging motor components as well as with major capsid protein, suggesting that pUL77 helps retain viral DNA during capsid assembly (19).…”
supporting
confidence: 69%
“…Mouse monoclonal antibody to ␣-tubulin (MA1 19401; Fisher Scientific, Waltham, MA) was used to confirm equal loading of SDS gels in IB experiments. For co-IP and IB in the infection setting, mouse monoclonal anti-UL93 antibody, kindly provided by Eva Maria Borst (18), mouse monoclonal anti-lamin A/C antibody (MA3 1000; Fisher Scientific, Waltham, MA), and rabbit anti-UL50, anti-UL53, and anti-UL97 antibodies, kindly provided by Don Coen (9), were used as the primary antibodies. Peroxidase-labeled goat anti-mouse IgG (PI31444; Fisher Scientific, Waltham, MA) or peroxidase-labeled goat anti-rabbit IgG (PI31460; Fisher Scientific, Waltham, MA) was used as the secondary antibody in IB.…”
Section: Cellsmentioning
confidence: 99%
“…Since no complementing cell lines are available to reconstitute the corresponding virus mutants, we applied the recently described adenovirus-mediated transfection protocol (adenofection) which allows direct investigation of BAC-transfected cells. During previous analyses, we have shown that upon adenofection, viral gene expression occurs with kinetics similar to that of infected cells, that the majority of adenofected cells successfully enters the late phase of the HCMV infection cycle, and that adenofection is well suited to study the consequences of deletion of various essential genes from the viral genome (18,46). Human telomerase reverse transcriptase-immortalized-RPE-1 cells (RPE-1 cells) were adenofected with the recombinant HCMV BAC genomes lacking either UL51, UL56, or UL89 or with the parental BAC pHG-UL51-SF/HA.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our data argue in favor of a model of the HCMV terminase as a multiprotein complex in which the individual subunits stabilize each other upon assembly. Such a setting was also proposed for other CMV protein complexes, namely, for the murine CMV (MCMV) US22 protein family (60) and for the HCMV major and small capsid proteins (18), as well as for the cellular anaphase-promoting complex, a multiprotein assembly targeted by HCMV (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation